ANALYSIS OF THE VOLUME OF PASSENGERS AND CARGO IN RAIL AND ROAD TRANSPORT IN POLAND IN 2009-2019 - Elżbieta MACIOSZEK (Scientific Journal of Silesian University of Technology. Series Transport, 2021)
Transport plays an important role in the economy of any country. Efficient and developed transport infrastructure of various modes of transport significantly affects the availability of transport services, and consequently, the well-being of citizens. This article presents an analysis of the volume of passengers and cargo transport using rail and road transport in Poland in 2009-2019. These analyses were carried out based on data obtained from the Central Statistical Office. All data concerns Polish entities that provide services in the field of passenger and freight transport in Poland and focuses on such information as the volume of passengers and cargo by individual means of transport, broken down into domestic and international transport. Further, the presented analyses concern the length of the available rail and road routes, tracks, the size of the rolling stock as well as the groups of transported loads.